Addition of four new records of Naidid (Oligochaeta) to the Iraqi fauna - Al-Abbad, M.Y.M. (Mesopotamian Journal of Marine Sciences, 2022)
The present study is concerned with the new records of oligochaete species to the Iraqi fauna. The oligochaete specimens were collected from shallow water of six sites on the bank of Shatt Al-Arab river, southern Iraq, during the period from March to August 2011. These oligochaetes were isolated from the surface layer of sediment and submerged plants. The species are Dero cooperi Stephenson, 1932, Dero sawayai Marcus, 1943, Pristinella idrensis (Sperber, 1948), and Pristinella notopora (Cernosvitov, 1937), they were recorded for the first time from Iraq. Measurements and the most important diagnostic features of these species were presented.